Ensino de química para alunos com deficiência visual : subsídios teóricos e práticos - Alves, Fernanda Iassenck de Matos (2018)
The general objective of this research was to contribute to the initial training of chemistry graduates, through a mini course which addresses some aspects about the teaching of chemistry for people with visual impairment. In this way, we elaborate and execute a minicourse for a Class II, Degree in Chemistry, from a Public University, with the following steps: reflection of historical and legislative concepts around visual impairment, discussion and exemplification of the multi- 1999) and the application of the thematic classes elaborated by the licenciandos for the students with visual deficiency that attends room of support. To assist us in the organization and analysis of the data obtained, we follow the heuristic path suggested by Content Analysis (BARDIN, 1977). The analysis of the initial interview showed that undergraduates presented great insecurity to teach a class for a visually impaired student and the belief that the phenomena of the natural sciences can only be understood through visual representations (seer culture). In the end, the mini-course of Teaching Chemistry for visually impaired students was able to make graduates more confident to interact with a visually impaired student, as well as breaking with the conception that it is only possible to learn through vision. However, he did not manage to consolidate the nine formative needs presented by Carvalho and Gil-Pérez (2011) and the nine inclusive teaching knowledge that Camargo (2012) lists